Infusoria cultivating methods using innovative medium for marine finfish larvae（FRGS17-034-0600); Final Report Fundamental Research Grant Scheme (FRGS) - Mukai, Yukinori; Mohammad Noor, Normawaty; Mohd Idris, Shaharah; Mustafa, Sufian (2019)
By batch culture method of objective 1, infusoria and Euplotes increased to the highest density during early culture periods such as 2-3 days. The infusoria were 2000- 6000 individuals /ml in the highest density of respective culture periods groups. The Euplotes were 50-900 individuals /ml in the highest density of respective culture period groups. By continuous culture method of objective 2, infusoria and Euplotes showed high densities in 5- 10 days, the highest density of infusoria was 2000-3000 individuals /ml in each harvesting group, and the highest density of Euplotes was also 2000-3000 individuals /ml in each harvesting group. 20% harvesting group was the highest total harvesting amount in both of infusoria and Euplotes. The results of objective 3 showed that the larvae of Asian seabass fed with mixed live feed (rotifers, Infusoria and Euplotes) had higher survival rates compared to other live feed groups. Larval rearing experiments of objective 4 of tiger grouper were conducted two times, in the first experiment, Euplotesmgroup showed the highest survival rate and in second experiment Protozoa (Infusoria) group showed the highest survival rates.